Analyzing Geoffrey Till’s Post Modern Navy Enabler of Defence Industry An Assessment of Leading Naval Industries in ASEAN - Suntud, Bodin (Defence Technology Academic Journal, 2022)
This article has three primary objectives. First, it attempts to revisit the analytical framework of Modern Navy and Post-Modern Navy offered by Geoffrey Till, the author of Seapower: A Guide for the Twenty-First Century. Second, it focuses on the enablers of the defence industry, especially the naval component, of Malaysia, Singapore, and Indonesia. Third, from studying the abovementioned navies, it outlines some policy recommendations for naval modernization in Thailand. It uses the SWOT method to assess the country’s overall industrial capability and opportunity. The source of these data derives from various academic works, online news and database, research and dissertations, all of which are academic open sources and are entirely not confidential. The sequence of this analysis stems from the theoretical framework of modern and post-modern navy and the next section is followed by proposing a thesis statement on an enabler of defence industry. This article uses this enabler to analyze the naval industries consecutively and comparatively. Then, it forecasts the trends of naval technology and business for the future. Some policy recommendations and organizational directions for Royal Thai Navy’s force modernization are discussed as potential outcomes of this research.